METHODS OF MEASUREMENT OF OIL QUANTITY IN TANKS - Fokeeva, Liya; Zainyllina1, Vilena (Revista Inclusiones, 2019)
In this article problems of accounting for the amount of oil in reservoirs are considered. Various types of oil storage tanks are analyzed, as well as devices for controlling its amount. Based on the studies conducted, the most appropriate level indicators were identified for their use in oil reservoirs of different types.